Resting state vagal tone in attention deficit (hyperactivity) disorder: a meta-analysis - Koenig, Julian; Kaess, Michael (The world journal of biological psychiatry, 2017)
Objectives: To quantify evidence on resting-state vagal activity in patients with attention deficit hyperactivity disorder (ADHD) relative to controls using meta-analysis.Methods: Three electronic databases (PubMed, PsycINFO, CINAHL Plus) were reviewed to identify studies. Studies reporting on any measure of short-term, vagally mediated heart rate variability during resting state in clinically diagnosed ADHD patients as well as non-ADHD healthy controls were eligible for inclusion.Results: Eight studies reporting on 587 participants met inclusion criteria. Random-effect meta-analysis revealed no significant main effect comparing individuals with ADHD (n = 317) and healthy controls (n = 270) (Hedges’ g = 0.06, 95% CI: 0.18-0.29, Z = 0.48, P = 0.63; k = 8). Sub-group analysis showed consistent results among studies in adults (k = 2) and children (k = 6) with ADHD.Conclusions: Unlike a variety of internalising psychiatric disorders, ADHD is not associated with altered short-term measures of resting-state vagal tone.